Health expenditure trajectory and gastric cancer incidence in the National Health Insurance Senior Cohort: a nested case-control study - Woo-Ri Lee; Ki-Bong Yoo; Jin-Won Noh; Minjee Lee (BMC, 2024)
Abstract Background Gastric cancer is the fourth most common cancer and highly prevalent in South Korea. As one of the predictors of gastric cancer, we focused on health utilization patterns and expenditures, as the surrogate variables of health conditions. This nested case-control study aimed to identify the association between health expenditure trajectory and incidence of gastric cancer. Methods Data from the National Health Insurance Service Senior Cohort of South Korea were used. Individuals diagnosed with gastric cancer (N = 14,873) were matched to a non-diagnosed group (N = 44,619) in a 1:3 ratio using a nested case-control design. A latent class trajectory analysis was performed to identify the patterns of health expenditure among the matched participants. Furthermore, conditional logistic regression analysis was conducted to examine the relationship between healthcare expenditure trajectories and gastric cancer incidence. Results Seven distinct health expenditure trajectories for five years were identified; consistently lowest (13.8%), rapidly increasing (5.9%), gradually increasing (13.8%), consistently second-highest (21.4%), middle-low (18.8%), gradually decreasing (13.1%), and consistently highest (13.2%). Compared to the middle-low group, individuals in the rapidly increasing [odds ratio (OR) = 2.11, 95% confidence interval (CI); 1.94-2.30], consistently lowest (OR = 1.40, 95% CI; 1.30-1.51), and gradually increasing (OR = 1.26, 95% CI; 1.17-1.35) groups exhibited a higher risk of developing gastric cancer. Conclusions Our findings suggest that health expenditure trajectories are predictors of gastric cancer. Potential risk groups can be identified by monitoring health expenditures.